(untitled) (Journal of Asian Development Studies, 2025)
The increasing complexity of global logistics networks has necessitated integrating advanced technologies to enhance transportation efficiency, reliability, and sustainability. This study investigated the application of geospatial Artificial Intelligence (AI) and machine learning to optimize transportation routes across urban, regional, and global networks. Using a quantitative research design, operational datasets from logistics firms were combined with satellite imagery and geospatial data to evaluate the effectiveness of AI-enabled predictive models, including convolutional neural networks (CNN) and reinforcement learning algorithms. Results demonstrated significant reductions in travel time and route distances, improved on-time delivery, and enhanced fuel efficiency, indicating operational and environmental benefits. Predictive models accurately forecast congestion and dynamically adjust routes, thereby enhancing reliability across diverse operational contexts. Furthermore, the study highlighted the potential of geospatial AI to reduce carbon emissions, aligning logistics operations with sustainability objectives. Challenges related to data quality, computational complexity, and model interpretability were identified, emphasizing the need for explainable AI solutions. Overall, the findings provide empirical evidence that AI-integrated geospatial analytics can transform traditional logistics networks into intelligent, adaptive, and environmentally conscious systems. The study offers practical insights for logistics managers and policymakers seeking to implement AI-driven optimization strategies while advancing sustainable supply chain management.